Evidence of a minority monoclinic LaNiO2.5 phase in lanthanum nickelate thin films. Issue 13 (20th March 2017) - López-Conesa, L.; Rebled, J. M.; Pesquera, D.; Dix, N.; Sánchez, F.; Herranz, G.; Fontcuberta, J.; Magén, C.; Casanove, M. J.; Estradé, S.; Peiró, F.
Abstract : LaNiO3 (LNO) thin films of 14 nm and 35 nm thicknesses grown epitaxially on LaAlO3 (LAO) and (LaAlO3 )0.3 (Sr2 TaAlO6 )0.7 (LSAT) substrates are studied using High Resolution Transmission Electron Microscopy (HRTEM) and High Angle Annular Dark Field (HAADF) imaging. Abstract : LaNiO3 (LNO) thin films of 14 nm and 35 nm thicknesses grown epitaxially on LaAlO3 (LAO) and (LaAlO3 )0.3 (Sr2 TaAlO6 )0.7 (LSAT) substrates are studied using High Resolution Transmission Electron Microscopy (HRTEM) and High Angle Annular Dark Field (HAADF) imaging. The strain state of the films is studied using Geometric Phase Analysis (GPA). Results show the successful in-plane adaptation of the films to the substrates, both in the compressive (LAO) and tensile (LSAT) cases. Through the systematic analysis of HRTEM superstructure contrast modulation along different crystal orientations, localized regions of the monoclinic LaNiO2.5 phase are detected in the 35 nm films.